Importance of repeated sampling: vegetation analyses after 10 years revealed different restoration trends in formerly extracted peatlands. Issue 3 (9th June 2022) - Pospíšilová, Petra; Vítovcová, Kamila; Prach, Karel
Abstract : The chronosequence approach, that is, analyses of several stages differing in age since disturbance or restoration but more or less comparable in site conditions, may well demonstrate, despite some limitations, a long‐term ecosystem development. Earlier, we described spontaneous vegetation succession in 11 differently aged industrially harvested raised bogs and suggested that spontaneous recovery of plant cover gradually proceeds toward the reference state of natural raised bogs. We repeated the analyses after 10 years and asked: (1) Are the successional trajectories of spontaneous restoration really directing toward reference natural sites? and (2) How do typical peatland plant species participate in re‐vegetation? Artificially afforested extracted peatland sites were used for comparison. We concluded that spontaneous recovery of plants does not proceed toward the reference sites. Instead it directs more toward the artificially afforested sites. Despite this, the spontaneously developed vegetation harbored many more peatland species. To turn the development toward the natural reference sites would require a substantial rise of the water table after ceasing peat extraction. The study demonstrates the importance of repeated analyses, which may give more reliable signs of the re‐vegetation direction than one‐time analyses.